The Role of Organizational Culture, Leadership Style, and Management Accounting Information Systems in Managerial Decision-Making Effectiveness: A Case Study of PT Garuda Indonesia Tbk, Yogyakarta Branch - Fadhilah Poodo; Nugraeni Nugraeni (Publikasi Indonesia, 2025)
This research aims to analyze the role of organizational culture, leadership style, and management accounting information systems (AIS) in supporting the effectiveness of managerial decision-making at PT Garuda Indonesia Tbk, Yogyakarta Branch Office. A qualitative case study approach was employed, utilizing secondary data from annual reports, financial statements, and official documents, supplemented by primary data collected through semi-structured interviews with branch managers. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, verified through source triangulation and member checking. The study findings revealed that an adaptive organizational culture encourages the involvement of ideas, work accuracy, and recognition of employee achievements. A transformational-participative leadership style facilitates timely decision-making by involving subordinates, providing motivation, and demonstrating accountability. Furthermore, a digitally integrated management accounting information system provides accurate, real-time, and relevant information, which supports strategic and operational decisions. These three aspects synergize to create a systematic, data-driven, and performance-oriented managerial decision-making process that enhances organizational effectiveness.